Sinantrópicos peçonhentos: sistema de notificação de acidentes e considerações biológicas - Barbosa, Abraão Ribeiro (2016)
Venomous animals share space with the human population, often causing fatal accidents. This fact is a public health problem that requires specific care and permanent and incisive measures. Most poisoning episodes occur in rural areas. However, urban areas are constantly affected, which characterizes the synanthropic profile of these animals. The differences between reporting data and biology of accidents culminated in underreporting which directly reflects in the epidemiology of the cases, as well as in the control, prevention and treatment of the accidents. This study aimed to describe the Epidemiological and Biological profile of accidents caused by venomous animals, registered in the National System of Disease Notification (SINAN), occurred in the metropolitan region of Campina Grande in Paraíba State, Brazil, in 2010 and 2015. Methodologically, we adopted the analyses of the injury reporting forms of the Toxicological Assistance Center (CEATOX), using the data available in the TabNet System (Ministry of Health), and animals that cause accidents, fixed and deposited in the collection of the CEATOX – Campina Grande. Three scientific articles, a scientific note of case reports, a chapter with recommendations to the SINAN, and a manual of good practices and identification of venomous animals were elaborated as result of this research. The main problem regarding the results was the imprecision in the identification of causative agents, which can not only underreport the data, but also limit the understanding of accidents, increasing the range of biological information on each case. Finally, it is concluded that investments in taxonomy and animal biology, as well as in the training of technical teams are indispensable for a more precise relation between these epidemiological events and the poisoning causative agent.